From Captives to Consuls : Three Sailors in Barbary and Their Self-Making across the Early American Republic, 1770-1840 - Goodin, Brett, 1987- (Book collections on Project MUSE., 2020)
"This book explores how three white American sailors who lived in the eighteenth and nineteenth centuries (Richard O'Brien, James Cathcart, and James Riley) turned their experiences of captivity in the Barbary States of North Africa into modest upward mobility in the form of diplomatic careers; their bids for betterment reflect important commercial, ideological, and diplomatic developments of the early American republic at a time when it began expanding westward"--